2018
DOI: 10.1021/acsami.8b01522
|View full text |Cite|
|
Sign up to set email alerts
|

Highly Biocompatible Chlorin e6-Loaded Chitosan Nanoparticles for Improved Photodynamic Cancer Therapy

Abstract: The photosensitizer Chlorin e6 (Ce6) has been frequently employed for photodynamic therapy (PDT) of cancer; however, its nonspecific toxicity has limited its clinical applications. In this study, we prepared chitosan nanoparticles (CNPs), with a mean diameter of approximately 130 nm, by a nonsolvent-aided counterion complexation method in an aqueous solution, into which Ce6 could be physically entrapped during the preparation process. These CNPs and Ce6-loaded CNPs (CNPs-Ce6) were fully characterized by UV-vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 39 publications
1
67
0
Order By: Relevance
“…Many investigations have found that the ROS levels in cancer cells are significantly associated with anticancer effect including proliferation inhibition and apoptosis induction. 30,[56][57][58][59] In order to explore the effect of Re-CDs on the inhibition of cancer cells, we measured the ROS level in A375 cells after they were treated with Re-CDs, by a flow cytometer. Results are displayed in Figure 6.…”
Section: Effect Of Re-cds On Ros Generation In Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigations have found that the ROS levels in cancer cells are significantly associated with anticancer effect including proliferation inhibition and apoptosis induction. 30,[56][57][58][59] In order to explore the effect of Re-CDs on the inhibition of cancer cells, we measured the ROS level in A375 cells after they were treated with Re-CDs, by a flow cytometer. Results are displayed in Figure 6.…”
Section: Effect Of Re-cds On Ros Generation In Cancer Cellsmentioning
confidence: 99%
“…High content of the ROS generated in cancer cells caused oxidative damage and apoptosis, therefore the Re-CDs showed desirable anticancer effect. 30,59,60 Different influences on the cell viabilities of cancer and normal cells might be related to the existence of Re-derived rare ginsenoside and the intracellular high-content imaging analysis for apoptosis and necrosis of cancer cells treated with re-cDs For further research about cell apoptosis and necrosis, after treating the cells with Re-CDs, Hoechst/PI double-staining method was applied in this experiment. 61 Hoechst 33342 could penetrate the cell membrane into cells, while PI could not enter the cells with normal construction of the cell membrane.…”
Section: Effect Of Re-cds On Ros Generation In Cancer Cellsmentioning
confidence: 99%
“…Chitin-based NG of doxorubicin can be used for various types of cancers including lungs, breast, liver, and prostate cancer [99]. Similarly, photosensitizer agent chlorin e6 has been recently used for the photodynamic therapy of cancer using chitosan-based NGs [100]. A descriptive detail of the anticancer applications of NGs is given in Table 1. 4.6.…”
Section: Diabetes Managementmentioning
confidence: 99%
“…Nanoparticles self-assembled by biopolymers, such as proteins and polysaccharides, have aroused great interests to deliver drugs or bioactive substances (Fioramonti, Perez, Aríngoli, Rubiolo, & Santiago, 2014;Gao, Tang, Gong et al, 2017;Jones & McClements, 2011) for their high availability, biocompatibility, nontoxicity, and biodegradability (Dai et al, 2018;Fioramonti et al, 2014). Sodium alginate (SA), a natural anionic polysaccharide, consisted of mannuronic (M) and guluronic (G) acid residues (Rahmani & Sheardown, 2018) has been extensively investigated for the applications in drug delivery (Agüeroa, Zaldivar-Silva, Peña, & Dias, 2017;Ding et al, 2018), 3D bioprinting (Axpe & Oyen, 2016), active substance encapsulation (Pandolfi, Pereira, Dufresne, & Legallais, 2017), tissue engineering (Reakasame & Boccaccini, 2018), and food industry. β-conglycinin (7S) is a major globulin of soy protein, and its isoelectric point is near 4.8.…”
Section: Practical Applicationsmentioning
confidence: 99%